2018
DOI: 10.1136/bcr-2018-224586
|View full text |Cite
|
Sign up to set email alerts
|

Negative myoclonus secondary to paroxetine intake

Abstract: Outside the context of overdose and serotonin syndrome, seizures and myoclonic movements attributed to selective serotonin reuptake inhibitors (SSRIs) are rare and poorly documented. We present a 77-year-old man, with no history of epilepsy, presenting in the emergency department with whole body jerks since that morning. Two days earlier, due to a prescription mistake, he was started on paroxetine 20 mg instead of his usual fluoxetine 20 mg. The patient's electroencephalogram (EEG), performed in the emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The mechanisms responsible for myoclonus are poorly understood, with increased serotonergic transmission, failure of the primary somatosensory cortex, and cerebellar impairment all implicated in its pathogenesis 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms responsible for myoclonus are poorly understood, with increased serotonergic transmission, failure of the primary somatosensory cortex, and cerebellar impairment all implicated in its pathogenesis 4 …”
Section: Discussionmentioning
confidence: 99%
“…3 The mechanisms responsible for myoclonus are poorly understood, with increased serotonergic transmission, failure of the primary somatosensory cortex, and cerebellar impairment all implicated in its pathogenesis. 4 A careful history that includes mapping the course of the illness, genetic information, other illnesses, and treatments and comprehensive neurological examination are invaluable for diagnosis. 5 Some authors have suggested using surface EMG recordings, 6 with EEG being considered, depending on the suspected site of origin of the myoclonus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to occur in West syndrome, [ 2 ] partial epilepsy, general epilepsy, or in other diseases or induced by some drugs. [ 3 8 ] ENM often occurs in the course of various types of epilepsy. Most ENM occurs after the diagnosis of benign childhood epilepsy with central temporal spikes (BECTS).…”
Section: Introductionmentioning
confidence: 99%